"This is What Democracy Really Looks Like!" Exploring Canoas, Rio Grande do Sul, Brazil. Issue 2 (June 2015) - Needleman, Ruth
<x xml:space="preserve">Abstract</x> Canoas, a city in southern Brazil, is innovating radical forms of democratic government in order to involve all residents in decision‐making for the city. Their achievements are so unprecedented that the United Nations awarded them a first prize for citizenship engagement. Tackling decades of exclusion, poverty, and pollution, the Mayor Jairo Jorge of the Workers' Party has led a restructuring of city government to facilitate a redistribution of wealth and power. This article examines this "new system of government, " highlighting programs, initiatives, and priorities for a sustainable economic development based on democratic participation and decision‐making.